Global agenda for livestock research. Proceedings of the consultation for the South-East Asia region - Devendra, C.; Gardiner, Peter R. (International Livestock Research Institute, 1995)
The papers presented here by the group covering the states of the Association of South East Asian Nations (ASEAN) had detailed discussions on defining the livestock priorities, research requirements, and ways to achieve these with a focus on Indonesia, Malaysia, the Philippines and Thailand. Discussions were conducted in three sequential phases. In the first phase, each country identified the priority agro-ecological zones (AEZs) and, within each, priority production systems in which livestock research was required. The results are presented in a tabular form. It was interesting that there was a consensual focus on the upland and lowland rainfed AEZs. Among the production systems, rice/buffalo and rice/cattle (beef and dairy), maize/buffalo and cattle systems, and the integration of ruminants with plantation crops (coconut, oil palm and rubber) were prominent. Phase two focused on specific researchable areas within production systems and within each country. They are summarised in detail in table 1. The most prominent priority research areas were feeding and nutrition, genetic improvement, methodologies for crop-animal interactions, and the promotion of the adoption of appropriate technologies. Phase three discussed the research requirements within individual countries. Notwithstanding the variable research capacity in NARS and the availability of funds, the general consensus among the countries was a requirement for the following: adequate funding for livestock research, training institutional strengthening, and germplasm conservation and use.